Issuer Credit Quality and the Price of Asset Backed Securities - Faltin-Traeger, Oliver; Johnson, Kathleen W; Mayer, Christopher (American Economic Review, 2010)
Issuer Credit Quality and the Price of Asset Backed Securities by Oliver Faltin-Traeger, Kathleen W. Johnson and Christopher Mayer. Published in volume 100, issue 2, pages 501-05 of American Economic Review, May 2010